Growth and Yield of Avicennia Officinalis (Baen) L. And Heritiera Fomes (Sundri) Buch. Ham. Plantations Established From Plus Tree Seeds in the Western Coastal Belt of Bangladesh (Journal of the Asiatic Society of Bangladesh, Science, 2020)
Abstract not availableJ. Asiat. Soc. Bangladesh, Sci. 46(2): 209-214, December 2020